Effectiveness of a Care Plan Based on the Multi-Theory Model in Reducing Fear of Disease Progression and Improving Quality of Life in Breast Cancer Patients: A Randomized Controlled Trial - Zhang J; Zhuang J; Chen X; Chu T; Zhang Q; Ma L; Zhou H; Wu Y; Chen L (Breast Cancer: Targets and Therapy)
Jiajia Zhang,1,* Jiaru Zhuang,1,* Xian Chen,1 Tianyu Chu,1 Qian Zhang,1 Linlin Ma,1 Hui Zhou,1 Yibo Wu,1 Ling Chen2 1Obstetrics, Gynecology and Reproduction Research Center, Affiliated Hospital of Jiangnan University, Wuxi, People’s Republic of China; 2Department of Breast Surgery, Affiliated Hospital of Jiangnan University, Wuxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yibo Wu, Obstetrics, Gynecology and Reproduction Research Center, Affiliated Hospital of Jiangnan University, Wuxi, 214062, People’s Republic of China, Email 9862016107@jiangnan.edu.cn Ling Chen, Department of Breast Surgery, Affiliated Hospital of Jiangnan University, Wuxi, 214062, People’s Republic of China, Email rainbow_lyn@163.comPurpose: Fear of progression has become a prominent mental health problem. Our research aimed to evaluate the effectiveness of a care plan based on the Multi-Theory Model of health behavior change in reducing fear of progression in breast cancer patients undergoing adjuvant chemotherapy.Patients and Methods: This randomized controlled trial enrolled 108 eligible participants receiving adjuvant chemotherapy at Jiangnan University Affiliated Hospital between May and December 2024. Routine care was administered to the control group, while the intervention group received the multi-theoretical model-based nursing intervention program integrated with general nursing. The evaluation time points included pre-intervention, immediately post-intervention (after 6 weeks), and 1-month post-intervention. Data were analyzed using Fisher’s exact test or chi-square test, Mann–Whitney U-test, independent samples t-test, generalized estimating equations, or repeated measures ANOVA.Results: At various post-intervention assessments, the Multi-Theory Model group demonstrated significantly lower fear of progression scores along with higher self-management efficacy and quality of life scores, compared to the control group (p < 0.05). There were time, between-group, and interaction effects for the differences in the total scores of quality of life, self-management efficacy, and fear of progression between the two groups of participants (p < 0.05).Conclusion: A nursing program grounded in the multi-theoretical model reduced the level of fear of progression, and improved quality of life and self-management efficacy in patients with breast cancer undergoing postoperative chemotherapy. These findings can provide a reference for psychological interventions in clinical settings for breast cancer patients.Keywords: the multi-theory model, breast cancer, self-management efficacy, quality of life, fear of progression